Love And Belongingness Need Reflected In F. Scott Fitzgerald's The Great Gatsby (1925)Novel: A Humanistic Approach - Iqbal, Muhammad, Dr. Phil. Dewi Candraningrum, M.Ed, Titis Setyabudi, S.S. M.Hum (2015)
This study is aimed to show the needs of love and belongingness in The Great Gatsby novel by using humanistic perspective. It is done by establishing objective, analyzing the novel based on it is structural elements and analyzing the novel based on humanistic analysis. This research is descriptive qualitative research. The object of the study is F. Scott Fitzgerald's The Great Gatsby (1925) novel published in 1925 by the Charles Scribner's Sons publisher. The data sources are divided into two namely primary data and secondary data. Primary data source is The Great Gatsby novel and the secondary data sources are other materials taken from books, journal, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusion. Based on humanistic analysis, Fitzgerald illustrates the need of love and belongingness affect and change the main character of the novel.